1998
DOI: 10.1038/sj.jim.2900472
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cr, Mo, Se and U by Desulfovibrio desulfuricans immobilized in polyacrylamide gels

Abstract: Intact cells of Desulfovibrio desulfuricans, immobilized in polyacrylamide gel, removed Cr, Mo, Se and U from solution by enzymatic-mediated reduction reactions. Lactate or H2 served as the electron donor and the oxidized Cr(VI), Mo(VI), Se(VI) and U(VI) served as electron acceptors. Reduction of the oxidized metal species resulted in the precipitation of solid phases of the metals. Metal removal efficiencies of 86-96% were achieved for initial concentrations of 1 mM Mo, Se, and U and 0.5 mM Cr. Insoluble meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 14 publications
4
63
1
1
Order By: Relevance
“…(g.h) -1 [22]. Pseudomonas fluorescens only reduced 95% of 0.2 mM selenate after 45 hours [23] and Desulvibrio desulfuricans took 25-37 hours to reduce 86% of 1 mM of selenate [24] which is much slower than what was observed in this study.…”
Section: Reduction Rate Experimentscontrasting
confidence: 55%
“…(g.h) -1 [22]. Pseudomonas fluorescens only reduced 95% of 0.2 mM selenate after 45 hours [23] and Desulvibrio desulfuricans took 25-37 hours to reduce 86% of 1 mM of selenate [24] which is much slower than what was observed in this study.…”
Section: Reduction Rate Experimentscontrasting
confidence: 55%
“…As an example, Figure S3 shows the dynamics of Desulfovibrio vulgaris, Geobacter metallireducens, and methanogenic archaea in water samples. The occurrence of these bacteria and archaea suggest a possibility of both direct enzymatically mediated microbial Cr(VI) reduction and an indirect Cr(VI) reduction through byproducts of microbial metabolism such as Fe 2+ and reactive sulfides (21,22,38,39).…”
Section: Resultsmentioning
confidence: 99%
“…(In this paper we characterize the microbial biomass using the total number of bacteria, which was determined using direct microscopy after acridine orange staining-AODC.) Although many bacterial strains are known to enhance reduction of Cr(VI) to Cr(III) both aerobically (17,18) and anaerobically (19)(20)(21)(22), only a few studies have examined the in situ potential of Cr(VI) microbial reduction in subsurface materials (e.g., [23][24][25]. Laboratory studies have also shown that Cr(VI) reduction in saturated soil aggregates under anaerobic conditions is mainly diffusion-rate-limited and can be strongly transport-controlled and localized (26,27).…”
Section: +mentioning
confidence: 99%
“…Many strains have been isolated that sorb (14,23,51,59,61), reduce (10,18,52,56), and precipitate (4,33,41,44,45) metals, usually on the outer membrane of the cell. Sorption is generally achieved in a reversible process and is dependent on the composition of the water being treated, as other chelating agents compete with the complexing moieties on the cell.…”
mentioning
confidence: 99%